Crystal structure of the PEG‐bound SH3 domain of myosin IB from Entamoeba histolytica reveals its mode of ligand recognition. Issue 8 (1st August 2017) - Gautam, Gunjan; Rehman, Syed Arif Abdul; Pandey, Preeti; Gourinath, Samudrala
Abstract : An in‐depth analysis of the PEG‐bound C‐terminal SH3 domain of myosin IB from Entamoeba histolytica has been performed, which reveals the mode of ligand recognition and will be helpful in the identification of probable binding partners of E. histolytica myosin IB. Abstract : The versatility in the recognition of various interacting proteins by the SH3 domain drives a variety of cellular functions. Here, the crystal structure of the C‐terminal SH3 domain of myosin IB from Entamoeba histolytica ( Eh MySH3) is reported at a resolution of 1.7 Å in native and PEG‐bound states. Comparisons with other structures indicated that the PEG molecules occupy protein–protein interaction pockets similar to those occupied by the peptides in other peptide‐bound SH3‐domain structures. Also, analysis of the PEG‐bound Eh MySH3 structure led to the recognition of two additional pockets, apart from the conventional polyproline and specificity pockets, that are important for ligand interaction. Molecular‐docking studies combined with various comparisons revealed structural similarity between Eh MySH3 and the SH3 domain of β‐Pix, and this similarity led to the prediction that Eh MySH3 preferentially binds targets containing type II‐like P XX P motifs. These studies expand the understanding of the Eh MySH3 domain and provide extensive structural knowledge, which is expected to help in predicting the interacting partners which function together with myosin IB during phagocytosis in E. histolytica infections.